Evaluation of Diagnostic Values of a Gender Discrimination Function, Based on Mandibular Dimorphic Parameters in Iranian Population - Farzaneh Ostovar Rad; Abbas Shokri; Bahareh Javanshi; Faezeh Kashi; Mahsa Fazilat (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate mandibular dimorphic parameters for sex determination by using panoramic radiographs and comparing the results with another equation. Material and Methods: In this analytical-descriptive study, the mandible variables, including the ramus height, the coronoid height, the mental height, and the distance between the right and left condyle, were measured in 326 panoramic radiographs. The discriminant function of the statistical method has previously been used to evaluate the diagnostic value of sex. The level of significance was considered 0.05. Results: The detection function obtained was statistically significant in quantitative correlation (p<0.001) with 99% agreement. Moreover, good sensitivity (81.72%), specify (80.25%), and moderate to good predictive values (PPV: 62.29 and NPV:91.6) were found. Among the mandibular parameters, chin height, ramus height, coronoid height, and distance between two condyles showed the highest gender dimorphism. Conclusion: Chin height, and ramus height have the most quality in gender dimorphism. A unique gender discrimination function has been obtained from the results.